A Case of Abdominal Sarcoidosis in a Patient with Acute Myeloid Leukemia. (28th February 2013) - Baskaran, Vadsala; Goodwin, Amanda; Athithan, Lavanya; Rinaldi, Ciro Roberto; Addeo, Alfredo
Abstract : The allogeneic bone marrow transplantation usually preceded by induction chemotherapy, in fit patients, represents the gold standard in the acute myeloid leukaemia. In the last years, many trials have been set up with the view of improving the number of remissions during the induction by adding new drugs. Several early or late side effects have been described in the literature. We herein present a patient with acute myeloid leukaemia patient who, after chemotherapy, developed ascites that turned out to be abdominal sarcoidosis.